Pengaruh Model Pembelajaran Problem Based Learning Dengan Modul Kontruktivisme Radikal Terhadap Hasil Belajar Peserta Didik - Riza Ulhaq*; Ismul Huda; Hafnati Rahmatan (Universitas Syiah Kuala, 2020)
The low students' learning achievement is one of the problems that is occurred in learning process that is caused by the inappropriate learning strategy that was applied in the classroom in delivering the lesson, therefore the expected goal cannot be achieved. Learning in the classroom should be able to guide the students to be more creative and independent through a series of scientific activity. The purpose of this study was to measure the effect of Problem Based Learning (PBL) models and radical constructivism module on students' learning outcome in the Madrasah Tsanawiyah, Banda Aceh. The data were collected since November 2019 until April 2020. The method used in this study was an experimental method with randomized post-test only control- group design. This research was conducted in two classes: experimental class with PBL model learning with radical constructivism module and the control class with PBL model learning only. The number of samples for this research were 160 students. The samples were chosen through random sampling method by observing the students’ chances in each class and the Madrasah as the experiment and control classes. The objective tests were used as an instrument to measure students' learning outcome. The data were collected through post-test about the pollution of environment. The independent sample t-test was used to test the hypotheses to see the effect of Problem Based Learning (PBL) models and radical constructivism module on students’ learning outcome. The results analysis based on the outcome learning score was the value of Sig 0,05, t valuet table, 4,741,97. Hence, the students who took part in learning PBL model and radical constructivism module showed significantly better in their learning outcomes compared to students who took part in learning PBL model only.